2016
DOI: 10.1186/s12958-016-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Different effectiveness of closed embryo culture system with time-lapse imaging (EmbryoScopeTM) in comparison to standard manual embryology in good and poor prognosis patients: a prospectively randomized pilot study

Abstract: BackgroundPreviously manual human embryology in many in vitro fertilization (IVF) centers is rapidly being replaced by closed embryo incubation systems with time-lapse imaging. Whether such systems perform comparably to manual embryology in different IVF patient populations has, however, never before been investigated.We, therefore, prospectively compared embryo quality following closed system culture with time-lapse photography (EmbryoScope™) and standard embryology.We performed a two-part prospectively rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…These results are in line with other studies, which showed similar results in good quality embryos, embryo development, blastocyst rate, implantation, and ongoing pregnancy rates between customary culture and TLS [14][15][16]. In the same way, in a two-part study, poor-prognosis patients have shown no diferences in Day-3 embryo quality, implantation, and clinical pregnancy rates between embryos cultured in EmbryoScope™ and conventional culture, whereas in the second portion, embryos developed in the EmbryoScope™ revealed signiicantly poorer quality on Day 3 compared to standard-cultured embryos [17]. Likewise, in a recent study, a total of 2092 embryos undergoing IVF cycles were evaluated by conventional morphology assessment or TLS.…”
Section: Arguments Against Predictive Value Of Tlsmentioning
confidence: 74%
“…These results are in line with other studies, which showed similar results in good quality embryos, embryo development, blastocyst rate, implantation, and ongoing pregnancy rates between customary culture and TLS [14][15][16]. In the same way, in a two-part study, poor-prognosis patients have shown no diferences in Day-3 embryo quality, implantation, and clinical pregnancy rates between embryos cultured in EmbryoScope™ and conventional culture, whereas in the second portion, embryos developed in the EmbryoScope™ revealed signiicantly poorer quality on Day 3 compared to standard-cultured embryos [17]. Likewise, in a recent study, a total of 2092 embryos undergoing IVF cycles were evaluated by conventional morphology assessment or TLS.…”
Section: Arguments Against Predictive Value Of Tlsmentioning
confidence: 74%
“…Three studies investigated the outcome of good quality embryo on Day 2/3[24, 26, 28], and no significant effect on this outcome was observed between TLI group and control group (RR 0.89, 95% CI 0.72–1.11, I2 = 42%, three studies, including 720 embryos). Results of pooled analysis of the oocyte-based review were showed in Fig 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, prospective studies are still needed to clarify algorithms for analyzing this data and proving, unequivocally, a significant benefit to patients [9]. Very recent randomized controlled trials have failed to show any benefit by adopting time lapse technology over morphology in improving pregnancy and delivery rates [13,14]. Fourth, we can consider modifying our protocols of ovarian stimulation to avoid the production of too many oocytes, which, as demonstrated here and in previous studies, may not lead to more live births, but to increased BEmbryo Wastages.M inimal stimulation or natural IVF cycles have been associated with improved egg quality and reduced aneuploidy rates [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Morphologic criteria to grade embryos correlate poorly with pregnancy and live birth rates and fail to identify chromosomally normal embryos [5][6][7]. The utilization of time-lapse embryo growth monitoring systems has also gained popularity, but data convincingly demonstrating improved outcomes as a result of this technology is still lacking [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%